The Influence of Digital Marketing and Campus Image on Student Decisions to Choose to Study at UKI Paulus Makassar - Eben Haezer Basran Patandean (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
This study aims to determine the effect of digital marketing media and campus image on students' decisions to continue their studies at UKI Paulus Makassar. The sample in this study was 100 first semester students who were continuing their studies at UKI Paulus Makassar. Data were analyzed using a quantitative approach using the SmartPLS application. Digital Marketing variable (X1) and campus image variable (X2) are independent variables in this study. The Student Decision Variable (Y) in choosing UKI Paulus as a place for them to continue their studies is the dependent variable in this research. From this study it is known that the use of digital marketing media (X1) has effect on students' decisions in choosing UKI Paulus as a place for them to continue their studies (Y). And, campus image (X2) has a positive and significant effect on student decisions (Y) in choosing UKI Paulus as a place for them to continue their studies. Based on the research results, the author suggests to the UKI Paulus Makassar campus to make more use of digital marketing as an alternative means of promotion to attract new students, in addition to continuing to improve the brand image of their campus in the eyes of prospective new students. Keywords:Digital Marketing, Brand Image, Consumer’s Decision, UKI Paulus